Volatility transmission between Dow Jones stock index and emerging Islamic stock index : case of subprime financial crises / Amir Saadaouia and Younes Boujelbene - Boujelbene, Younes (Faculty of Business and Management, 2015)
In the course of the recent global crisis, the stock shocks are distributed and transmitted from their homes in the developed stock market to emerging stock markets. By supporting the development of emerging stock markets, this study aims to see the transmission of volatility between the Dow Jones stock index and the Dow Jones emerging Islamic stock indiex. In this study we have divided the period into three, periods, before, during and after this crisis to demonstrate the resilience of the Islamic market index in response to the global financial crisis. Another aim of this study is to provide a new guide line for investors in emerging stock market before making investment decisions. The data are daily, going from 02/01/2005 until 31/12/2012. To measure the transmission we used bivariate BEKK-GARCH and DCC-GARCH model. The result shows that there is a transmission mainly during the crisis period which means that the crisis affects all the financial assets whether Islamic or not. The same result also shows the preference to invest in both Islamic and classical stock indexes since they are less risky. Keywords: Volatility transmission, DJ Index, Islamic DJ Emerging Index, Subprime crisis.